Controlled Synthesis of Calcium Tungstate Microstructures with Different Morphologies in an AOT/TEA/H2O System - Bao, Keyan; Guo, Ge; Sun, Hongxian; Yan, Jiawei; Xing, Wenru; Ding, Chenghua (Asian Journal of Chemistry, 2010)
Calcium tungstate micro-crystallites with dumbbell-like morphologies were prepared in triethanolamine-water mixed solution system, employing AOT as surfactant. It is found that the morphologies of CaWO4 are mostly affected by the concentration of AOT and the volume ratio of triethanolamine-water. For example, by adjusting the volume ratio of triethanolamine-water and the concentration of AOT, ellipsoid- and orange-like CaWO4 micro-crystallites could be controlled synthesized. Room-temperature photoluminescence measurements showed that the prepared CaWO4 micro-crystallite had a strong dark blue peak at 429 nm or blue emission peak at 448 nm, which indicated their potential application as electro-optic devices.